Case Report: An atypical case of ARPKD highlights the utility and challenges of implementing genetic testing in cystic kidney disease - Marquez, Jonathan; Hawkins, Lauren M.; Beck, Anita E.; Dipple, Katrina M.; Glass, Ian A.; Keefe, Alexandra C.; Nguyen, Elizabeth D. (Frontiers in Pediatrics, 2025)
BackgroundBiallelic pathogenic variants in PKHD1 cause a highly heterogenous disease, predominantly involving the kidneys and liver. Although the correlation between genotype and phenotype remains unclear, many variants in this gene have been described.CaseIn this study, we describe a case of suspected autosomal recessive polycystic kidney disease (ARPKD) due to a novel variant in PKHD1. The patient in this instance presented with a novel PKHD1 variant (c.2713C>A; p.Gln905Lys) in trans with a previously described pathogenic variant (c.7994T>C; p.Leu2665Pro).ConclusionsThe PKHD1 variant c.2713C>A; p.Gln905Lys may contribute to an ARPKD phenotype with a delayed juvenile onset.